Keseimbangan Kerja Keluarga pada Perempuan Bekerja: Tinjauan Teori Border - Arri Handayani (Buletin Psikologi, 2013)
Nowadays, working women are common phenomena. However, the involvement of women in the working career has both positive and negative impacts for the individual women, their family andtheir organisation as well. To minimize those negative impacts, these working women are required to balance their roles both in working and family ranahs. Border theory was used for discussing thework family balance, with the assumption that the interaction between working environment and family environment is the central focus of the border theory. In this case, an individual womantries to appropriately manage the working and family environments in order to maintain the balance. Efforts that have been made include managing the involvement at work and in the family,and making proper communication between her husband and her employer about the problem at work and in the family.